Crossword puzzles for chemistry education: learning goals beyond vocabulary. Issue 3 (19th April 2016) - Yuriev, Elizabeth; Capuano, Ben; Short, Jennifer L.
Abstract : Chemistry is a technical scientific discipline strongly underpinned by its own complex and diverse language. To be successful in the problem-solving aspects of chemistry, students must master the language of chemistry, and in particular, the definition of terms and concepts. To assist students in this challenging task, a variety of instructional techniques need to be explored. In this study we have developed crossword puzzles to aid students in mastering chemical terminology via meaningful learning as opposed to rote memorisation. We have evaluated this tool for its effectiveness in study and revision. Specifically, we asked: (i) are crosswords effective as in-class and out-of-class revision tools? (ii) Is crossword performance (as a measure of the command of scientific vocabulary) predictive of problem-solving ability? The results demonstrated that crossword puzzles improve the ability of students to solve problems and, when used systematically, contribute to increases in learning. The findings are discussed in the context of information processing and meaningful learning.